MahÄrah KalÄm Book: The Implementation at Arabic Course - Cholifah, Nur; Akmalia, Frida (Departemen Pendidikan Bahasa Arab, 2021)
In this study, the researchers focus on implementing mahÄrah kalÄm book at Al-Azhar Arabic course, Pare. This study used a descriptive qualitative approach.Â The data were collected using observation, interviews, and documentation. Miles and Huberman techniques were used to analyzing the data. The results reveal that: first, the textbooks used are books compiled directly by the founder of the course. There are al-muhÄdaá¹¡ah 1, mufradÄt 1500 vocabularies, and al-qawÄid al-taysÄ«r. Second, in the learning process, the teacher used various methods, namely conversation, singing, question answering, and memorization. Third, the daily evaluation of speaking skills is in the form of a test that requires the students to make a story, which should be memorized and then practiced in front of the class. Finally, the final evaluation covers all the materials learned within 5 -10 minutes.